The social networks of young people in Ireland with experience of long‐term foster care: some lessons for policy and practice. Issue 3 (9th May 2012) - Mc Mahon, Conor; Curtin, Chris
ABSTRACT This paper presents findings from the first study of the social networks of a group of young people in Ireland who have experienced long‐term foster care. The study group was composed of two groups of young people, a group who were currently in care and a group who had left the care system. The central focus was to examine the impact of foster care on the social network experience of the young people. Findings indicated that foster care impacts on the young people's social network experience in the following ways: losing contact with extended family; a greater challenge in making and sustaining friendships; an impact on education; and an inability to maintain contact with groups and activities that are of significance. This paper also presents recommendations in relation to policy and practice, including the raising of awareness of the importance of a social network approach in working with young people with care experience.